Pengaruh Jenis Aktivator Adsorben Abu Boiler Pabrik Kelapa Sawit Terhadap Mutu Minyak Sawit Mentah - Ika Ucha Pradifta Rangkuti; Heri Purwanto; Hilda Sry Utami Pohan (The University of Lampung, 2021)
Palm oil mill boiler ash is one of the substances that can be used as an adsorbent. The adsorbent can absorb certain components of a fluid phase, which before being applied needs to be activated using chemicals so that the effectiveness of the absorption is increasing. The use of adsorbents in CPO is quite effective in maintaining its quality. Several previous studies have studied the application of adsorbents in maintaining the quality of CPO. The purpose of the study was to utilize palm oil mill boiler ash as an adsorbent of several types of activators and to determine the effect of effective activator types in application to the quality of CPO oil. This study used a non-factorial completely randomized design with adsorbent activation treatment using H3PO4 and NaCl with a concentration of 10% and soaked for 24 hours. There are 3 parameters observed in the adsorbent application to CPO, namely free fatty acids, water content, and dirt content. The results showed that the adsorbent activated with H3PO4 was an effective adsorbent with a decrease in its free fatty acids up to 0.43%, water content decreased to 0.07%, but an increase in CPO impurities content of 0.24%. While the adsorbent activated using NaCl showed free fatty acids 0.22%, water content decreased by 0.03% and dirt content also increased by 0.24%. Keywords: adsorbent activator, crude palm oil, boiler ash, H3po4, Nacl